Long-term survival of stage Ib lung adenocarcinoma with postoperative brain oligometastasis: a case report and literature review - Xu, Kai; Feng, Xing; Wang, Limin; Du, Quan; Jin, Er (Folia Neuropathologica, 2024)
Lung adenocarcinoma remains one of the most frequent and deadly tumour entities. Early-stage lung adenocarcinoma is extremely difficult to detect and is also easy to recur or metastasize after treatment. Since the new adenocarcinoma classification was presented in 2011, several studies have shown that patients with solid and/or micropapillary (S/MP) predominant patterns showed a worse prognosis. Here we report the case of a 54-year-old woman who was diagnosed with stage Ib lung adenocarcinoma with S/MP components and developed an isolated brain oligometastasis after resection and adjuvant therapy. A craniocerebral operation was performed, combined with radiotherapy and targeted therapy, and the patient eventually achieved a good quality of life. Our work reviews the clinical features of lung cancer complicated with S/MP components, the relationship between MP and epidermal growth factor receptor (EGFR) mutation, as well as treatment strategies for such a patient with postoperative brain oligometastasis of lung adenocarcinoma complicated with EGFR Exon19del mutation.